Physiological and Proteomic Analysis of Penicillium digitatum in Response to X33 Antifungal Extract Treatment - Lin, Shu-Hua; Luo, Pan; Yuan, En; Zhu, Xiangdong; Zhang, Bin; Wu, Xiaoyu (Frontiers in Microbiology, 2020)
Abstract Penicillium digitatum is a widespread pathogen among Rutaceae species that causes severe fruit decay symptoms on infected citrus fruit (known as citrus green mold). The employment of fungicides can effectively control the citrus green mold, significantly reducing agricultural economic loss. In this study, we found that the X33 antifungal metabolite produced by Streptomyces lavendulae strain X33 dose-dependently inhibited the mycelial growth of P. digitatum. Additionally, physiological and proteomic analysis strategies were applied to explore the inhibitory mechanism of the X33 antifungal metabolite of the S. lavendulae strain X33 on the mycelial growth of P. digitatum. A total of 277 differentially expressed proteins, consisting of 207 upregulated and 70 downregulated, were identified from the comparative proteomics analysis. The results indicated that the X33 antifungal metabolite induced mitochondrial membrane dysfunction and cellular integrity impairment, which can affect energy metabolism, oxidative stress, and transmembrane transport. The improved alkaline phosphatase activity and extracellular conductivity, increased H2O2 and malondialdehyde contents, and inhibition of energy, amino acid, and sugar metabolism indicated that the oxidative stress of P. digitatum is induced by the X33 antifungal metabolite. These findings provided insight into the antifungal mechanism of the X33 antifungal metabolite against P. digitatum by suggesting that it may be an effective fungicide for controlling citrus postharvest green mold.